STUDI DESKRIPTIF DUA KOMBINASI ANTIPSIKOTIK DAN SINDROM PARKINSONISME DALAM PENGOBATAN SKIZOFRENIA PARANOID - noor cahaya; Herningtyas Nautika Lingga; Riska Novisra Nasution; Bella Na Fhory (JCPS (Journal of Current Pharmaceutical Sciences), 2020)
Schizophrenia is the most common psychotic disorders. Incidence rate 1-2% in the population counted from populations who have experienced the condition. The most common type is paranoid schizophrenia. Antipsychotic combination therapy is widely used in schizophrenia. There are some problems in schizophrenia therapy due to antipsychotics use, one of them is parkinsonism as a side effect of treatment. The aimed of the research was to identified the combination therapy and symptoms of parkinsonism experienced by paranoid schizophrenia patients who use therapy with 2 combinations of antipsychotics. This was a descriptive study, retrospective data collection technique using 93 medical records in 2018 period. The results showed the use of 2 types of antipsychotic combinations,haloperidol-chlorpromazine (44.1%) and haloperidol-risperidone (55.9%) combinations. The number of patients who experienced parkinsonism on haloperidol-chlorpromazine combination therapy (N = 41) was 20 patients and who did not experience 21 patients. Whereas in the combination therapy of haloperidol-risperidone (N = 52), there were 16 patients with parkinsonism and 36 patients who did not. Parkinsonism experienced by patients include hypersaliva; muscle tremors and rigidity. Percentage of parkinsonism in haloperidol-chlorpromazine combination therapy, including hypersaliva 42%; 50% tremor and 8% muscle rigidity. In the haloperidol-risperidone combination group, hypersaliva was 61%; tremor 15% and muscle rigidity 24%. The conclusion obtained from the results of the study is the percentage of parkinsonism in haloperidol-chlorpromazine combination therapy is greater than haloperidol-risperidone combination therapy.